1994
DOI: 10.1128/aac.38.10.2330
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the Listeria tetracycline resistance gene tet(S) in Enterococcus faecalis

Abstract: Two hundred thirty-eight tetracycline-and minocycline-resistant clinical isolates of Enterococcus and Streptococcus spp. were investigated by dot blot hybridization for the presence of nucleotide sequences related to tet(S) (first detected in Listeria monocytogenes BM4210), tet(K), tet(L), tet(M), tet(O), tet(P), and tet(Q) genes. The tet(S) determinant was found in 22 strains of Enterococcus faecalis, associated with tet(M) in 9 of these isolates and further associated with tet(L) in 3 of these strains. tet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 37 publications
2
36
0
3
Order By: Relevance
“…The different tet genes can have either the same mode of action (efflux or ribosomal protection), or different modes of action (efflux and ribosomal protection), just like the pathogenic and opportunistic species do (230). The carriage of multiple tet genes of different classes is commonly found in individual gram-positive isolates (37,236,266,267,307) and in Mycobacterium spp. and Streptomyces spp.…”
Section: Incidence Of Tetracycline Resistancementioning
confidence: 99%
“…The different tet genes can have either the same mode of action (efflux or ribosomal protection), or different modes of action (efflux and ribosomal protection), just like the pathogenic and opportunistic species do (230). The carriage of multiple tet genes of different classes is commonly found in individual gram-positive isolates (37,236,266,267,307) and in Mycobacterium spp. and Streptomyces spp.…”
Section: Incidence Of Tetracycline Resistancementioning
confidence: 99%
“…The tet(S) gene is originally known from a Listeria monocytogenes plasmid (Charpentier et al, 1993) but subsequently, it has been found on the chromosome of Enterococcus faecalis (Charpentier et al, 1994;Francois et al, 1997) and on the conjugative plasmid of Lactococcus spp. (Perreten, 1997).…”
Section: Ribosomal Protection Determinantsmentioning
confidence: 99%
“…Few more broad-host-range plasmids with ability of conjugative transfer of resistance to L monocytogenes such as pAMb1 of Enterococcus faecalis and pIP823 have been reported (37,75).…”
Section: Kratak Sadržajmentioning
confidence: 99%
“…Even though multi-resistant strains are not frequently isolated, evidence of their presence is available (204). Given the current wide use of antibiotics in food production and clinics, isolation of L. monocytogenes with reduced antibiotic susceptibility is expected to grow.Ever since the first antibiotic-resistant strain was described in France in1988 (176) Antibiotic resistance in L. monocytogenes is mostly due three mobile genetic elements: selftransferable plasmids, mobilizable plasmids, and conjugative transposons (37,40,97,176,177).Efflux pumps have also been reported to be present in Listeria (86). …”
mentioning
confidence: 99%
See 1 more Smart Citation